Peningkatan Literasi Fiskal Masyarakat Sipil melalui Sekolah Anggaran: Mendorong Efisiensi dan Transparansi Belanja APBD Lombok Timur 2025 - Sandy Ari Wijaya; Usnadi Usnadi; Purnama Hadi Kusuma; Abdul Rahman Salman Paris; Widya Hartati; Ratna Yuniarti (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service (PkM) activity aimed to enhance the capacity of civil society to conduct effective public oversight of the East Lombok Regency Regional Revenue and Expenditure Budget (APBD) for fiscal year 2025. The “Budget School” program, organized by the Pimpinan Daerah Pemuda Muhammadiyah in collaboration with the Indonesian Forum for Budget Transparency (FITRA) NTB and ITSKes Muhammadiyah Selong, provided participants with a comprehensive and critical analysis of the regional budget structure and allocation patterns. The key findings highlighted notable fiscal inefficiencies, particularly the disproportionately high allocation for Employee Spending (Belanja Pegawai), which indicates an urgent need for budget reallocation toward increasing Capital Expenditure (Belanja Modal). Such realignment is essential to accelerate infrastructure development, enhance public service delivery, and ensure broader socio-economic benefits for the community. The event, conducted on September 25, 2025, successfully improved fiscal literacy among youth and civil society actors by strengthening their understanding of fiscal governance and legal oversight mechanisms. Overall, the activity fostered collective awareness and encouraged active participation in promoting sustainable, transparent, and efficient regional financial management.